High-water-absorption porous gel foam material and preparation method thereof

By using cellulose nanofiber dispersion and specific monomers to carry out acid-base reaction and ultraviolet cross-linking under normal pressure, a porous gel foam material with high water absorption is successfully prepared, solving the high preparation cost and complex process in the prior art. The problem of this achieves high efficiency, low cost production of materials and excellent water absorption performance.

CN119463285AActive Publication Date: 2025-02-18ZHEJIANG SCI-TECH UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411399807.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-09
Publication Date
2025-02-18
Estimated Expiration
2044-10-09

AI Technical Summary

Technical Problem

The prior art is difficult to prepare high-water absorption porous gel foam materials at low cost and efficiently under normal pressure, resulting in high production costs and complex processes.

Method used

Using cellulose nanofiber dispersion as the matrix, acrylic acid, acrylamide and methylcellulose are dispersed and dissolved, and a crosslinking agent and photoinitiator are added to form foam through acid-base reaction, and crosslinking is carried out by ultraviolet radiation, and finally in normal times. Dry under pressure.

Benefits of technology

The high-water absorption porous gel foam material is prepared under normal pressure at low cost and simple process. The material has high water absorption capacity and stable moisture absorption properties. The cellulose nanofibers reinforce the strength of the material and the stability of the pore structure.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119463285A_ABST
    Figure CN119463285A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of hydrogel foam materials, in particular to a preparation method of a high-water-absorption porous gel foam material. The method specifically comprises the following steps: sequentially dispersing and dissolving acrylic acid, acrylamide and methyl cellulose into cellulose nanofiber dispersion liquid to obtain prefabricated liquid A; dissolving sodium bicarbonate in the cellulose nanofiber dispersion liquid in a saturated manner, adding a photoinitiator, and uniformly mixing to obtain a pre-prepared liquid B; the prefabricated liquid A and the prefabricated liquid B are injected into the same sealed container according to the volume ratio of 1: 1 to be mixed, and foam is generated through reaction; then carrying out ultraviolet radiation treatment on the foam, and carrying out radiation crosslinking reaction on the foam to obtain gel foam; and finally, soaking the obtained gel foam in a mixed solution of glycerol and ethanol, taking out, draining, and drying at normal pressure to obtain the high-water-absorption porous gel foam material. The preparation method does not involve complex equipment, the technological process is simple and easy to implement, and the prepared foam material has high water absorption.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of hydrogel foam materials, and in particular to a porous gel foam material with high water absorption rate and a preparation method thereof. Background Art

[0002] Highly absorbent materials can absorb and fix dozens or even hundreds of times their own water. Due to their high water absorption and swelling capacity, they are widely used in industry and agriculture. Highly absorbent foam materials with an overall porous structure not only have superb water absorption performance, but also have the advantages of strong structural integrity, high safety in use, and fast water absorption speed, which makes this material have unique advantages in many fields such as medical care, food industry, etc.

[0003] Gel foam is a type of polymer porous material with high hydrophilicity and overall porous structure, and can be used as a highly absorbent material. While maintaining its original physical and chemical properties, gel foam has an overall porous structure of 10-1000 μm continuous bubbles and a porosity of more than 80%, which brings the advantages of low density, excellent absorption performance, and large surface area to gel foam. At the same time, the gel material itself can provide biodegradability, biocompatibility, antibacterial properties and other functions, and has broad application prospects.

[0004] Gel foam materials are usually prepared by treating hydrogels with freeze drying or supercritical drying methods. Through the drying process under specific conditions, the water in the hydrogel is removed and a continuous porous structure is formed. The freeze drying method is carried out by freezing the hydrogel below the eutectic temperature and removing the water in the hydrogel by sublimation under a vacuum environment. It has the disadvantages of long process time and high energy consumption. Supercritical drying uses liquid CO2 to replace the water in the gel, and forms a porous structure after releasing the liquid CO2 in the supercritical state. It has the limitations of harsh preparation conditions and high equipment requirements. Both methods cannot be carried out under normal pressure, so the resulting preparation cost is high, which limits the large-scale low-cost application of gel foam materials. In contrast, if gel foam materials can be prepared by drying under normal pressure, the production cost of such materials will be effectively reduced and their market expansion will be helpful.

[0005] At present, the preparation of gel foam by atmospheric pressure drying is to adjust the specific hydrogel composition or structure, design a special support structure to overcome the mesh collapse caused by surface tension during the drying process, or take additional auxiliary methods to reduce the surface tension to improve the material quality. These all have limitations in cost, process conditions and application.

[0006] Therefore, it is necessary to develop a low-cost and simple preparation method for the preparation of gel foam materials. Summary of the invention

[0007] In order to solve the above technical problems, the present invention proposes a method for preparing a porous gel foam material with high water absorption rate which is low in cost and simple to prepare. This method is carried out under normal pressure, which not only has low preparation cost but also simple process, and has important practical significance and application value.

[0008] The technical solution adopted by the present invention to solve its technical problem is: A method for preparing a porous gel foam material with high water absorption rate, the preparation method specifically comprising the following steps: (1) dispersing and dissolving acrylic acid, acrylamide and methyl cellulose in a cellulose nanofiber dispersion having a solid content of 0.5-2% in sequence; the total molar concentration of acrylic acid and acrylamide is 7-8 mol / L; finally, adding a crosslinking agent to the mixed dispersion and mixing evenly to obtain a preformed liquid A; the mass of methyl cellulose accounts for 0.1-0.3% of the total mass of the preformed liquid A; (2) saturating sodium bicarbonate in a cellulose nanofiber dispersion having a solid content of 0.5-2%, and then adding a photoinitiator to the mixed dispersion and mixing them evenly to obtain a preformed solution B; (3) Preformed liquid A and preformed liquid B are injected into the same sealed container at a volume ratio of 1:1 through a dual-channel syringe and mixed, and the two react with acid and base in the sealed container to generate foam; (4) subjecting the foam in the sealed container of step (3) to ultraviolet radiation treatment to undergo a radiation cross-linking reaction to obtain a gel foam; (5) Soaking the gel foam obtained in step (4) in a mixed solution of glycerol and ethanol for more than 3 hours, finally taking it out, draining it, and drying it at normal pressure to obtain a porous gel foam material with high water absorption rate.

[0009] Preferably, in step (1), the molar ratio of acrylic acid to acrylamide is 1-6:1.

[0010] Preferably, the cross-linking agent in step (1) is polyethylene glycol diacrylate.

[0011] Preferably, the amount of the cross-linking agent added in step (1) is 4-6% of the mass of acrylic acid and acrylamide.

[0012] Preferably, the photoinitiator in step (2) is 2-hydroxy-2-methyl-1-phenyl-1-propanone.

[0013] Preferably, the amount of photoinitiator added in step (2) is 0.2-2% by volume of the preformed liquid B.

[0014] A porous gel foam material with high water absorption rate is prepared by adopting the above-mentioned preparation method.

[0015] In the above scheme of the present invention, cellulose nanofibers are small in size, large in specific surface area, high in crystallinity, and rich in free hydroxyl groups. They have applications in the fields of increasing mechanical strength, hydrogen bond crosslinking, and self-assembly, and can enhance the main material, expanding the controllable range of mechanical properties and the application field. Cellulose nanofibers can enhance the skeleton of the gel, and their supporting effect is more excellent. Relying on the excellent supporting effect, the normal pressure drying of the hydrogel is achieved. The gel foam has a foam structure while maintaining its own characteristics, so that it has a strong water absorption performance.

[0016] Compared with the prior art, the present invention has the following beneficial effects: (1) The preparation method of the present invention effectively reduces the preparation cost of gel foam materials, has low energy consumption, does not involve complex equipment, has a simple and easy process, and has a short synthesis preparation time (90-150s), and is expected to be mass-produced under normal pressure conditions.

[0017] (2) The gel foam material prepared by the present invention has a large water absorption capacity and stable moisture absorption performance. The presence of cellulose nanofibers significantly improves the strength of the gel and ensures that the pore structure of the material does not collapse when it is dried at normal pressure. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 This is a physical picture of the gel foam material prepared according to the present invention.

[0019] Figure 2 This is a scanning electron microscope comparison diagram of the gel foam material prepared in the present invention.

[0020] Figure 3 This is a comparison diagram of the normal pressure drying of the gel foam material prepared by the present invention before and after modification.

[0021] Figure 4 This is a comparison chart of the mechanical properties of the foam materials of Example 2 of the present invention and Comparative Example 2 at 25°C. DETAILED DESCRIPTION

[0022] The technical scheme of the present invention is further described in detail below through specific embodiments. In the present invention, unless otherwise specified, the methods in the following embodiments are all conventional methods in the art.

[0023] The present invention mainly provides a method for preparing a porous gel foam material with high water absorption rate, and the preparation method specifically comprises the following steps: (1) dispersing and dissolving acrylic acid, acrylamide and methyl cellulose in a cellulose nanofiber dispersion having a solid content of 0.5-2% in sequence; the total molar concentration of acrylic acid and acrylamide is 7-8 mol / L; finally, adding a crosslinking agent to the mixed dispersion and mixing evenly to obtain a preformed liquid A; the mass of methyl cellulose accounts for 0.1-0.3% of the total mass of the preformed liquid A; wherein the molar ratio of acrylic acid to acrylamide is 1-6:1; the crosslinking agent is polyethylene glycol diacrylate, and the amount added is 4-6% of the total mass of acrylic acid and acrylamide; (2) saturating sodium bicarbonate in a cellulose nanofiber dispersion having a solid content of 0.5-2%, and then adding a photoinitiator to the mixed dispersion and mixing evenly to obtain a preformed liquid B; the photoinitiator is 2-hydroxy-2-methyl-1-phenyl-1-propanone, and the amount added is 0.2-2% by volume of the preformed liquid B; (3) Preformed liquid A and preformed liquid B are injected into the same sealed container at a volume ratio of 1:1 through a dual-channel syringe and mixed, and the two react with acid and base in the sealed container to generate foam; (4) subjecting the foam in the sealed container of step (3) to ultraviolet radiation treatment to undergo a radiation cross-linking reaction to obtain a gel foam; (5) Soaking the gel foam obtained in step (4) in a mixed solution of glycerol and ethanol for more than 3 hours, finally taking it out, draining it, and drying it at normal pressure to obtain a porous gel foam material with high water absorption rate.

[0024] Embodiment 1: A porous gel foam material with high water absorption rate, the specific preparation steps of which are as follows: (1) 3.9 g acrylic acid, 3.8 g acrylamide and 0.05 g methyl cellulose were dissolved in 10 mL cellulose nanofiber dispersion, and then a crosslinking agent, polyethylene glycol diacrylate, was added, and the crosslinking agent accounted for 4% of the total weight of the monomers. The mixture was mixed evenly to obtain preformed solution A; (2) NaHCO3 was saturated and dissolved in 15 mL of cellulose nanofiber dispersion, and then 30 μL of photoinitiator was added. The photoinitiator was 2-hydroxy-2-methyl-1-phenyl-1-propanone, and the added amount was 0.2% by volume of preformed liquid B. The mixture was mixed evenly to obtain preformed liquid B; (3) Inject preformed solutions A and B into the sealed bag using a dual-channel syringe; (4) The foam in the sealed bag was irradiated with a 200 W ultraviolet lamp at 30°C for 120 seconds to complete radiation crosslinking; (5) The obtained gel foam is immersed in a mixed solution of glycerol and ethanol in a volume ratio of 10 / 90, and finally dried at normal pressure to obtain a porous gel foam material with high water absorption rate.

[0025] Embodiment 2: A porous gel foam material with high water absorption rate, the specific preparation steps of which are as follows: (1) 5.8 g acrylic acid, 2.0 g acrylamide and 0.05 g methyl cellulose were dissolved in 10 mL cellulose nanofiber dispersion, and then a cross-linking agent polyethylene glycol diacrylate was added, with the cross-linking agent accounting for 5% of the total weight of the monomers, and mixed evenly to obtain preformed solution A; (2) NaHCO3 was saturated and dissolved in 15 mL of cellulose nanofiber dispersion, and then 150 μL of photoinitiator was added. The photoinitiator was 2-hydroxy-2-methyl-1-phenyl-1-propanone, and the added amount was 1% by volume of preformed liquid B. The mixture was mixed evenly to obtain preformed liquid B; (3) Inject preformed solutions A and B into the sealed bag using a dual-channel syringe; (4) The foam in the sealed bag was irradiated with a 200 W ultraviolet lamp at 30°C for 120 seconds to complete radiation crosslinking; (5) The obtained gel foam is immersed in a mixed solution of glycerol and ethanol in a volume ratio of 10 / 90, and finally dried at normal pressure to obtain a porous gel foam material with high water absorption rate.

[0026] Embodiment 3: A porous gel foam material with high water absorption rate, the specific preparation steps of which are as follows: (1) 6.6 g acrylic acid, 1.1 g acrylamide and 0.05 g methyl cellulose were dissolved in 9 mL cellulose nanofiber dispersion, and then a cross-linking agent, polyethylene glycol diacrylate, was added, and the cross-linking agent accounted for 6% of the total weight of the monomers. The mixture was mixed evenly to obtain preformed solution A; (2) NaHCO3 was saturated and dissolved in 15 mL of cellulose nanofiber dispersion, and then 300 μL of photoinitiator was added. The photoinitiator was 2-hydroxy-2-methyl-1-phenyl-1-propanone, and the added amount was 2% by volume of preformed liquid B. The mixture was mixed evenly to obtain preformed liquid B; (3) Inject preformed solutions A and B into the sealed bag using a dual-channel syringe; (4) The foam in the sealed bag was irradiated with a 200 W ultraviolet lamp at 30°C for 120 seconds to complete radiation crosslinking; (5) The obtained gel foam is immersed in a mixed solution of glycerol and ethanol in a volume ratio of 10 / 90, and finally dried at normal pressure to obtain a porous gel foam material with high water absorption rate.

[0027] Embodiment 4: A porous gel foam material with high water absorption rate, the specific preparation steps of which are as follows: (1) 5.8 g acrylic acid, 2.0 g acrylamide and 0.03 g methyl cellulose were dissolved in 9 mL cellulose nanofiber dispersion, and then a cross-linking agent polyethylene glycol diacrylate was added, with the cross-linking agent accounting for 5% of the total weight of the monomers, and mixed evenly to obtain preformed solution A; (2) NaHCO3 was saturated and dissolved in 15 mL of cellulose nanofiber dispersion, and then 75 μL of photoinitiator was added. The photoinitiator was 2-hydroxy-2-methyl-1-phenyl-1-propanone, and the added amount was 0.5% by volume of preformed liquid B. The mixture was mixed evenly to obtain preformed liquid B; (3) Inject preformed solutions A and B into the sealed bag using a dual-channel syringe; (4) The foam in the sealed bag was irradiated with a 200 W ultraviolet lamp at 30°C for 120 seconds to complete radiation crosslinking; (5) The obtained gel foam is immersed in a mixed solution of glycerol and ethanol in a volume ratio of 10 / 90, and finally dried at normal pressure to obtain a porous gel foam material with high water absorption rate.

[0028] Embodiment 5: A porous gel foam material with high water absorption rate, the specific preparation steps of which are as follows: (1) 5.8 g acrylic acid, 2.0 g acrylamide and 0.02 g methyl cellulose were dissolved in 9 mL cellulose nanofiber dispersion, and then a cross-linking agent polyethylene glycol diacrylate was added, with the cross-linking agent accounting for 5% of the total weight of the monomers, and the mixture was mixed evenly to obtain preformed solution A; (2) NaHCO3 was saturated and dissolved in 15 mL of cellulose nanofiber dispersion, and then 75 μL of photoinitiator was added. The photoinitiator was 2-hydroxy-2-methyl-1-phenyl-1-propanone, and the added amount was 0.5% by volume of preformed liquid B. The mixture was mixed evenly to obtain preformed liquid B; (3) Inject preformed solutions A and B into the sealed bag using a dual-channel syringe; (4) The foam in the sealed bag was irradiated with a 200 W ultraviolet lamp at 30°C for 120 seconds to complete radiation crosslinking; (5) The obtained gel foam is immersed in a mixed solution of glycerol and ethanol in a volume ratio of 10 / 90, and finally dried at normal pressure to obtain a porous gel foam material with high water absorption rate.

[0029] Comparative Example 1: The preparation method of the material of this comparative example specifically comprises the following steps: (1) Dissolve 5.8 g acrylic acid, 2.0 g acrylamide and 0.05 g methyl cellulose in 10 mL deionized water, then add crosslinking agent polyethylene glycol diacrylate, the crosslinking agent accounts for 5% of the total weight of the monomers, and mix well to obtain preformed liquid A; (2) Dissolve NaHCO3 in 15 mL of deionized water, then add 150 μL of photoinitiator, the photoinitiator is 2-hydroxy-2-methyl-1-phenyl-1-propanone, the added amount is 1% by volume of preformed liquid B. Mix well to obtain preformed liquid B; (3) Inject preformed solutions A and B into the sealed bag using a dual-channel syringe; (4) The foam in the sealed bag was irradiated with a 200 W ultraviolet lamp at 30°C for 120 seconds to complete radiation crosslinking; (5) The obtained gel foam is immersed in a mixed solution of glycerol and ethanol in a volume ratio of 10 / 90, and finally dried at normal pressure to obtain the gel foam.

[0030] Comparative Example 2: The preparation method of the material of this comparative example specifically comprises the following steps: (1) 3.9 g acrylic acid, 3.8 g acrylamide and 0.05 g methyl cellulose were dissolved in 10 mL cellulose nanofiber dispersion, and then a cross-linking agent polyethylene glycol diacrylate was added, with the cross-linking agent accounting for 5% of the total weight of the monomers, and the mixture was mixed evenly to obtain preformed solution A; (2) NaHCO3 was saturated and dissolved in 15 mL of cellulose nanofibers, and then 150 μL of photoinitiator was added. The photoinitiator was 2-hydroxy-2-methyl-1-phenyl-1-propanone, and the added amount was 1% by volume of preformed liquid B. The mixture was mixed evenly to obtain preformed liquid B; (3) Inject preformed solutions A and B into the sealed bag using a dual-channel syringe; (4) The foam in the sealed bag was irradiated with a 200 W ultraviolet lamp at 30°C for 120 seconds to complete radiation crosslinking; (5) Drying at normal pressure yields gel foam.

[0031] The water absorption performance of the gel foam of the present invention was tested, and the morphology after normal pressure drying was compared with that of Comparative Example 1. The results are shown in the following table.

[0032] Comparison table of water absorption performance at 25 ℃: Water absorption time Example 1 Example 2 Example 3 Example 4 Example 5 Comparative Example 1 Comparative Example 2 0 1 1 1 1 1 1 1 1min 14 11 10 15 13 12 10 2min 26 29 21 27 25 16 14 3min 36 39 31 38 36 21 22 4min 42 48 40 44 46 30 25 The foam moisture content (R) in the table is calculated by the following formula: ; in: M1 is the mass of foam gel after absorbing water, M0 is the original mass of the foam gel.

[0033] Through the analysis of the data in the above table, it can be seen that the water absorption of the gel foam material obtained in Examples 1, 2, and 3 is not much different, indicating that the material absorption performance obtained within the monomer concentration range described is stable. Examples 2, 4, and 5 show that when the amount of methyl cellulose added reaches a certain value, the gel foam can remain intact. Comparative Example 1 does not add cellulose nanofibers, and the water absorption performance of the product is poor, indicating that cellulose nanofibers have a stabilizing effect on the skeleton of the gel foam and can ensure that the pore structure of the gel foam remains good. The material obtained in Comparative Example 2 has not been soaked in glycerol ethanol, and the water absorption performance is poor, indicating that glycerol ethanol has a stabilizing effect on the pore structure of the gel foam during the normal pressure drying process.

[0034] like Figure 2 As shown in the figure, the mechanical properties comparison at 25 ℃.

[0035] right Figure 4 Analysis shows that the gel foam materials obtained in Comparative Example 1 and Example 2 are compressed to 80% of their size at a compression rate of 50 μm / s. In Comparative Example 1, no cellulose nanofibers are added, water is used as the solvent, and the other addition amounts are the same as those in Example 2. From the curve comparison, it can be clearly seen that Example 2 has higher compression strength and better flexibility, and the cellulose nanofibers can strengthen the skeleton of the gel, and its supporting effect is more excellent.

[0036] As can be seen from the above table, the water absorption of the gel foam of the present invention is better than that of the original foam product. The comprehensive moisture absorption of the product and the state after drying indicate that the product can be dried at normal pressure and has excellent water absorption function ( Figure 3 The gel foam of the present invention has good strength and water absorption effect, and the raw materials are cheap, the equipment requirements are low, the operation is simple, and it has the potential for mass production and commercialization.

[0037] It is obvious to those skilled in the art that the above embodiments are not intended to be exhaustive or limit the embodiments to the specific precise forms disclosed. It is obvious to those skilled in the art that certain modifications, combinations and variations can be made based on the above teachings.

Claims

1. A method for preparing a porous gel foam material with high water absorption, characterized in that: The preparation method specifically comprises the following steps: (1) dispersing and dissolving acrylic acid, acrylamide and methyl cellulose in a cellulose nanofiber dispersion having a solid content of 0.5-2% in sequence; the total molar concentration of acrylic acid and acrylamide is 7-8 mol / L; finally, adding a crosslinking agent to the mixed dispersion and mixing evenly to obtain a preformed liquid A; the mass of methyl cellulose accounts for 0.1-0.3% of the total mass of the preformed liquid A; (2) saturating sodium bicarbonate in a cellulose nanofiber dispersion having a solid content of 0.5-2%, and then adding a photoinitiator to the mixed dispersion and mixing them evenly to obtain a preformed solution B; (3) Preformed liquid A and preformed liquid B are injected into the same sealed container at a volume ratio of 1:1 through a dual-channel syringe and mixed, and the two react with acid and base in the sealed container to generate foam; (4) subjecting the foam in the sealed container of step (3) to ultraviolet radiation treatment to undergo a radiation cross-linking reaction to obtain a gel foam; (5) Soaking the gel foam obtained in step (4) in a mixed solution of glycerol and ethanol for more than 3 hours, finally taking it out, draining it, and drying it at normal pressure to obtain a porous gel foam material with high water absorption rate.

2. The method for preparing a porous gel foam material with high water absorption rate according to claim 1, characterized in that: In step (1), the molar ratio of acrylic acid to acrylamide is 1-6:

1.

3. The method for preparing a porous gel foam material with high water absorption rate according to claim 1 or 2, characterized in that: The cross-linking agent in step (1) is polyethylene glycol diacrylate.

4. The method for preparing a porous gel foam material with high water absorption rate according to claim 1, characterized in that: The amount of the cross-linking agent added in step (1) is 4-6% of the total mass of acrylic acid and acrylamide.

5. The method for preparing a porous gel foam material with high water absorption rate according to claim 1, characterized in that: The photoinitiator in step (2) is 2-hydroxy-2-methyl-1-phenyl-1-propanone.

6. The method for preparing a porous gel foam material with high water absorption rate according to claim 1, characterized in that: In step (2), the amount of photoinitiator added is 0.2-2% by volume of the preformed liquid B.

7. A porous gel foam material with high water absorption, characterized in that: The foam material is prepared by the preparation method described in any one of claims 1 to 6 above.

Citation Information

Patent Citations

  • Starch-based porous hydrogel and preparation method thereof

    CN103923428A

  • Normal-pressure drying preparation method of nanocellulose aerogel

    CN118667219A

  • Superabsorbent polymer composite comprising a superabsorbent polymer and cellulosic nanofibrils

    US20110301027A1

  • Super absorbent hydrogel foams

    US5750585A

  • AU8554101A